Ecological Validity of Impulsive Choice: Consequences of Profitability-Based Short-Sighted Evaluation in the Producer-Scrounger Resource Competition - Ogura, Yukiko; Amita, Hidetoshi; Matsushima, Toshiya (Frontiers in Applied Mathematics and Statistics, 2018)
Results of intertemporal choice paradigm have been accounted for mostly by psychological terms such as temporal discounting of subjective value. Inability to wait for delayed gratification (choice impulsiveness, as opposed to self-control) is often taken to represent violated rationality. If viewed from foraging ecology, however, such impulsiveness can be accountable as adaptive adjustments to requirements in nature. First, under the circumstance where foragers stochastically encounter food items, the optimal diet-menu model suggests that each option must be evaluated by profitability (e/h), which is the ratio of energetic gain (e) per handling time (h), a short-sighted currency. As h includes the delay, profitability will be hyperbolically lower for long-delay food. Second, because of the resource competition between producing and scrounging foragers, profitability of the producer’s gain will critically depend on the scrounger’s behaviors. We first constructed an analytical model. The model predicted that the profitability of small and short-delay food option (SS) can be higher than that of the large and long-delay alternative (LL), depending on the duration in which the producer can monopolize a food patch (finder’s share). Next, we conducted numerical simulations on the assumption of variable food amount in each patch with realistic set of behavioral parameters. Although non-linearity of profitability function largely reduced profitability for variable amount of food, SS still can have a higher profitability than LL when the finder’s share is small. Because SS is consumed more quickly, it is more resistant against scrounging than LL. In good accordance, foraging domestic chicks form a synchronized flock and show socially-facilitated investment of effort. If raised in competition, chicks develop a higher degree of choice impulsiveness.